Sinergitas konsep pang pada payu dan good governance dalam mengatasi sengketa kredit macet pada lembaga perkreditan desa - Sara, I Made (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research explores the principle of pang on payu as a supporting dimension for the implementation of good governance in the settlement of bad credit disputes at the Village Credit Institution (LPD) Desa “X” in Bali. By using a phenomenological approach, the results of this research show that the principle of pang di payu is effective in supporting the implementation of good governance in LPDs, especially in the case of bad credit disputes. Further findings show that, firstly, the principle of pang di payu is the most appropriate means to build synergy between LPDs and the community, and secondly, this principle is able to increase the credibility of LPDs. The Village Credit Institution requires the application of good governance supported by the principle of pang di payu to protect its sustainability from the